SELF LEADERSHIP IN THE FORMATION OF SANTRI INDEPENDENCE IN PONDOK PESANTREN TAHFIDZ LEADERSHIP NUR AL RAHMAN - Siti Hamidah Kristiana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
This study aims to explain the implementation of self-leadership training and follow-up training in establishing the independence of students. Self-leadership is very important to be had by students in order to have the habit of being independent in leading themselves before leading others. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation. While the data analysis technique was carried out by data analysis techniques using interactive data analysis, namely data reduction, data presentation, and drawing conclusions and verification. The results showed that Nur Al Rahman's Tahfizh Leadership Islamic Boarding School was very committed and serious in educating the leadership of the students so that the students' independence was formed, especially the ability to enforce discipline over themselves. This is evidenced by the existence of clear and gradual phases to achieve it, namely; self-leadership training, personal behavior change, building an Islamic personality, and regular social action as a form of personality development. All stages are going well and can be seen in the formation of students' independence. Apart from that, it is also supported by a rote program whose success or not really depends on the independence of the students. So objectively, the students change their own behavior to be more positive, productive, and contributive. and regular social action as a form of personality development. All stages are going well and can be seen in the formation of students' independence. Apart from that, it is also supported by a rote program whose success or not really depends on the independence of the students. So objectively, the students change their own behavior to be more positive, productive, and contributive. and regular social action as a form of personality development. All stages are going well and can be seen in the formation of students' independence. Apart from that, it is also supported by a rote program whose success or not really depends on the independence of the students. So objectively, the students change their own behavior to be more positive, productive, and contributive.